PENGEMBANGAN BAHAN AJAR MATAKULIAH DESAIN DAN STRATEGI PEMBELAJARAN - triasih wahyu hartati (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
The compulsory subject in the health and recreation physical education study program of IKIP Budi Utomo is the Design and Learning Strategy course. Learning achievement for the Design and Learning Strategy courses is that students are able to make physical education learning design in accordance with the characteristics of students and school infrastructure in accordance with the norms. adequate. But in reality the Lecturer in Design and Learning Strategy has never developed teaching materials that specifically discuss the Design and Learning Strategies of Physical Education with the character of virtue. Students also admitted that it was difficult to find design references and physical education learning strategies that use Indonesian. Most references use English so that students find it difficult to understand. The method of this research is development research using a 4D model consisting of define, design, develop, and disseminate. The results of this development research are the availability of teaching materials in the Design and Learning Strategies with the character of virtue that has been valid and can be implemented for students of Physical Health and Recreation Education (PJKR) at IKIP Budi Utomo.